Toxicidade de sedimentos contaminados por rejeitos da mineração no Rio Doce em embriões do Zebrafish (Danio rerio) - Thais Victoria Pires de Almeida (2022)
Despite its economic importance, mining is responsible for several socio-environmental problems, being considered one of the main human activities that contribute to metal pollution in watersheds. Heavy metals from mining waste have great potential for bioaccumulation and biomagnification in the food chain, being responsible for causing cytotoxic and genotoxic effects in organisms. The objective of the study was to evaluate the effects of acute exposure to sediments from the Rio Doce contaminated by mining tailings from the Fundão dam. For this, contact tests were carried out with Danio rerio embryos during 96 h of exposure. Sediments from 3 contaminated points on the Doce River and one point on the Piranga River, not contaminated by tailings (reference point), were used. For negative control, one group was exposed to inert, uncontaminated sediment, totaling 5 groups. Mortality rates, malformations and hatching of embryos, sensory, physiological and skeletal parameters, metallotinein (MT), heat shock protein (HSP) 70, acetylcholinesterase (AChE), cell proliferation and death, and caspase-3 were evaluated. Metal analysis showed the presence of As, Cr, Cu, Hg and Ni above the limits recommended by CONAMA. Embryos exposed to sediment showed a significantly higher mortality rate than the control and a significantly lower hatching rate. Skeletal, physiological and sensory alterations, neurotoxic effects, increased AChE activity and reduced spontaneous movements were observed mainly at the points closest to the dam. Furthermore, contamination significantly increased MT, HSP70 immunoexpression and altered cell proliferation and death activities. These results show that the Doce river sediment remains cytotoxic even 6 years after the Fundão dam rupture, negatively affecting the embryonic development of zebrafish, and, consequently, could compromise the structure of fish populations in the Doce river basin.